Pelatihan Penciptaan Lagu Anak-Anak Berbasis Kearifan Lokal bagi Guru Sekolah Dasar - Putra, Zakarias Aria Widyatama; Ghozali, Imam; Djau, Nurmila Sari; Olendo, Yudhistira Oscar; Sagala, Mastri Dihita; Grandena, Egi Putri; Silaban, Chiristianly Yery; Muniir, Asfar (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Introducing songs to children can hone their sensitivity, literacy skills, and language diversity. Introducing children's songs through their creation based on local wisdom can also be a form of preservation of their culture. The PKM objective of this training program is for elementary school teachers in Sukadana, North Kayong, to have basic skills in making children's songs based on the identity and characteristics of the region. The training methods used are lectures, questions and answers, demonstrations, practices, simulations, and reflections. The results of the PKM children's song creation training program are that there are approximately 15 elementary school teachers who are enthusiastic about making children's songs with the rules and musical elements that have been taught. In addition, various themes of children's songs based on local wisdom have been explicitly and implicitly written in song lyrics for the 2–5 grade range.